Spinal tuberculosis: proposed spinal infection multidisciplinary management project (SIMP) flow chart revision - Vanino, E; Tadolini, M; Evangelisti, G; Zamparini, E; Attard, L; Scolz, K; Terzi, S; Barbanti Brodano, G; Girolami, M; Pipola, V; Gasbarrini, A; Viale, P (European review for medical and pharmacological sciences, 2020)
We propose a revised flow chart of spinal infection multidisciplinary management project (SIMP) aimed to standardize the diagnostic process and management of spinal tuberculosis (TB). We reviewed data from all TB cases with osteoarticular involvement treated at a large tertiary teaching hospital in Bologna, Northern Italy, from January 2013 to December 2017. We cross-linked notified osteoarticular TB cases with SIMP database and we analysed clinical, diagnostic, and treatment data of all cases managed by SIMP. Osteoarticular TB accounted for the 7.8% (n=40) of all TB cases notified between 2013 and 2017 (N=513). Among the identified cases, 52% (n=21/40) had spine involvement: all were enrolled and evaluated by SIMP multidisciplinary group. Females accounted for 57% (12/21) of patients, the median age was 52 years (range 24-82). In the 67% (n=14/21) of cases, the major clinical symptom of spinal TB was back pain reported for a median of 4.5 months (range 1-12 months) before hospital admission. The interferon gamma release assay was positive in 75% (n=16/21) of patients. All patients performed MRI with gadolinium, which indicated spondylodiscitis in 90%. 18F-FDG-PET/CT revealed average maximum standardized uptake value (SUV max) of 12.54 (range 5.3-22) in 17/19 (89.5%). Bacteriological confirmation of TB was obtained in 86% of cases (n=18/21). One-third of patients (7/21) underwent surgery and 95% successfully completed the anti-TB treatment. Our data reveal that a multidisciplinary approach to spine tuberculosis facilitates early and accurate diagnosis and can improve medical and surgical management of this disease.